Answer:
13 years old
Step-by-step explanation:
2x - 4
11-5=6
6 x 2 = 12
12 - 4 = 8
8 + 5 = 13
CHECKING JUST TO MAKE SURE:
13 - 5 = 8
11 - 5 = 6
6 x 2 = 12
12 - 8 = 4
You can now tell that it is correct.
Lilies :
![390 - 268 - 74 = 48](https://tex.z-dn.net/?f=390%20-%20268%20-%2074%20%3D%2048)
![48 \times 5 = 240](https://tex.z-dn.net/?f=48%20%5Ctimes%205%20%3D%20240)
Total number of lilies the florist will buy next week = 240
Hope this helps. - M
The first trigonometric expression cot x and sin x in terms of the second expression is one over tan x and one over cosec x.
<h3>What is trigonometry?</h3>
Trigonometry deals with the relationship between the sides and angles of a right-angle triangle.
Write the first trigonometric expression in terms of the second expression.
The cotangent can be written as
![\cot x= \dfrac{1}{\tan x}](https://tex.z-dn.net/?f=%5Ccot%20x%3D%20%5Cdfrac%7B1%7D%7B%5Ctan%20x%7D)
And the sine can be written as
![\sin x = \dfrac{1}{\csc x}](https://tex.z-dn.net/?f=%5Csin%20x%20%3D%20%5Cdfrac%7B1%7D%7B%5Ccsc%20x%7D)
More about the trigonometry link is given below.
brainly.com/question/22698523
#SPJ4
C. The square root of 144
Answer:
See explanation
Step-by-step explanation:
There are three possible cases:
1. Point N lies between M and P, then MN + NP = MP. Consider needed difference:
![\dfrac{MN}{NP}-\dfrac{MN}{MP}=\dfrac{MN}{NP}-\dfrac{MN}{MN+NP}=\dfrac{MN(MN+NP)-MN\cdot NP}{NP(MN+NP)}=\\ \\=\dfrac{MN^2+MN\cdot NP-MN\cdot NP}{NP(MN+NP)}=\dfrac{MN^2}{NP(MN+NP)}](https://tex.z-dn.net/?f=%5Cdfrac%7BMN%7D%7BNP%7D-%5Cdfrac%7BMN%7D%7BMP%7D%3D%5Cdfrac%7BMN%7D%7BNP%7D-%5Cdfrac%7BMN%7D%7BMN%2BNP%7D%3D%5Cdfrac%7BMN%28MN%2BNP%29-MN%5Ccdot%20NP%7D%7BNP%28MN%2BNP%29%7D%3D%5C%5C%20%5C%5C%3D%5Cdfrac%7BMN%5E2%2BMN%5Ccdot%20NP-MN%5Ccdot%20NP%7D%7BNP%28MN%2BNP%29%7D%3D%5Cdfrac%7BMN%5E2%7D%7BNP%28MN%2BNP%29%7D)
2. Point N lies to the right from point P, then MP + PN = MN. Consider needed difference:
![\dfrac{MN}{NP}-\dfrac{MN}{MP}=\dfrac{MP+PN}{NP}-\dfrac{MP+PN}{MP}=\dfrac{MP}{NP}+1-1-\dfrac{NP}{MP}=\dfrac{MP^2-NP^2}{NP\cdot MP}](https://tex.z-dn.net/?f=%5Cdfrac%7BMN%7D%7BNP%7D-%5Cdfrac%7BMN%7D%7BMP%7D%3D%5Cdfrac%7BMP%2BPN%7D%7BNP%7D-%5Cdfrac%7BMP%2BPN%7D%7BMP%7D%3D%5Cdfrac%7BMP%7D%7BNP%7D%2B1-1-%5Cdfrac%7BNP%7D%7BMP%7D%3D%5Cdfrac%7BMP%5E2-NP%5E2%7D%7BNP%5Ccdot%20MP%7D)
3. Point N lies to the left from point M, then NM + MP = NP. Consider needed difference:
![\dfrac{MN}{NP}-\dfrac{MN}{MP}=\dfrac{MN}{MN+MP}-\dfrac{MN}{MP}=\dfrac{MN\cdot MP-MN(MN+MP)}{MP(MN+MP)}=\\ \\=\dfrac{MN\cdot MP-MN^2-MN\cdot MP}{MP(MN+MP)}=\dfrac{-MN^2}{MP(MN+MP)}](https://tex.z-dn.net/?f=%5Cdfrac%7BMN%7D%7BNP%7D-%5Cdfrac%7BMN%7D%7BMP%7D%3D%5Cdfrac%7BMN%7D%7BMN%2BMP%7D-%5Cdfrac%7BMN%7D%7BMP%7D%3D%5Cdfrac%7BMN%5Ccdot%20MP-MN%28MN%2BMP%29%7D%7BMP%28MN%2BMP%29%7D%3D%5C%5C%20%5C%5C%3D%5Cdfrac%7BMN%5Ccdot%20MP-MN%5E2-MN%5Ccdot%20MP%7D%7BMP%28MN%2BMP%29%7D%3D%5Cdfrac%7B-MN%5E2%7D%7BMP%28MN%2BMP%29%7D)